Atypical, slowly progressive behavioural variant frontotemporal dementia associated with C9ORF72 hexanucleotide expansion. Issue 4 (7th March 2012) - Khan, Baber K; Yokoyama, Jennifer S; Takada, Leonel T; Sha, Sharon J; Rutherford, Nicola J; Fong, Jamie C; Karydas, Anna M; Wu, Teresa; Ketelle, Robin S; Baker, Matthew C; Hernandez, Mariely-Dejesus; Coppola, Giovanni; et al.
Abstract : Background: Some patients meeting behavioural variant frontotemporal dementia (bvFTD) diagnostic criteria progress slowly and plateau at mild symptom severity. Such patients have mild neuropsychological and functional impairments, lack characteristic bvFTD brain atrophy and have thus been referred to as bvFTD 'phenocopies' or slowly progressive (bvFTD-SP). The few patients with bvFTD-SP that have been studied at autopsy have demonstrated no evidence of FTD pathology, suggesting that bvFTD-SP is neuropathologically distinct from other forms of FTD. Here, two patients with bvFTD-SP with chromosome 9 open reading frame 72 (C9ORF72) hexanucleotide expansions are described. Methods: 384 patients with an FTD clinical spectrum and Alzheimer's disease diagnoses were screened for C9ORF72 expansion. Two bvFTD-SP mutation carriers were identified. Neuropsychological and functional data, as well as brain atrophy patterns, assessed using voxel based morphometry (VBM), were compared with 44 patients with sporadic bvFTD and 85 healthy controls. Results: Both patients were aged 48 years at baseline and met possible bvFTD criteria. In the first patient, VBM revealed thalamic and posterior insula atrophy. Over 7 years, his neuropsychological performance and brain atrophy remained stable. In the second patient, VBM revealed cortical atrophy with subtle frontal and insular volume loss. Over 2 years, her neuropsychological and functional scores as well as brain atrophy remained stable. Conclusions: C9ORF72 mutations can present with a bvFTD-SP phenotype. Some bvFTD-SP patients may have neurodegenerative pathology, and C9ORF72 mutations should be considered in patients with bvFTD-SP and a family history of dementia or motor neuron disease.